Short communication: Y-STR sample haplotypes from five United States of America population groups - Michelle L. Pignone; April M. Manzella; Michelle Galusha; Jennifer Le; Lilliana I. Moreno (Forensic Science International: Reports, 2022)
Y-STR haplotype data from five relevant United States population groups are provided. These data have been shared with the Y-Chromosome Haplotype Reference Database (YHRD) and are relevant for forensic casework statistics, genetic studies and other applicable forensic investigations.